Sosialisasi Pola Hidup Bersih dan Sehat melalui Giat Bersih Lingkungan Pemukiman Transmigran Kecamatan Ledo - Apindiati, Rita Kurnia (Lembaga Dongan Dosen, 2023)
A clean and healthy lifestyle (PHBS) is an individual or collective effort related to health behavior with the aim of improving the level of public health. The aim of this community service activity (PKM) is to socialize PHBS through actively cleaning up rubbish in residential areas and public facilities, as well as PHBS educational lectures related to how to stop the breeding of mosquitoes as vectors of various types of viral diseases, as well as factors that must be considered to supports the achievement of a better level of health. All residents in the Transmigrant area of ​​Suka Jaya Village, Ledo District, took part in active cleaning activities, by cleaning each area of ​​the house and its surroundings, while the educational lecture was attended by 20 participants as representatives of the community. The results of the activity show that there has been an increase in the community's ability to process waste in their respective environments as well as knowledge in breaking the chain of mosquito breeding in residents' environments.